Early osteoarthritis of the trapeziometacarpal joint is not associated with joint instability during typical isometric loading - Halilaj, Eni; Moore, Douglas C.; Patel, Tarpit K.; Ladd, Amy L.; Weiss, Arnold-Peter C.; Crisco, Joseph J. (Journal of orthopaedic research, 2015)
ABSTRACT The saddle‐shaped trapeziometacarpal (TMC) joint contributes importantly to the function of the human thumb. A balance between mobility and stability is essential in this joint, which experiences high loads and is prone to osteoarthritis (OA). Since instability is considered a risk factor for TMC OA, we assessed TMC joint instability during the execution of three isometric functional tasks (key pinch, jar grasp, and jar twist) in 76 patients with early TMC OA and 44 asymptomatic controls. Computed tomography images were acquired while subjects held their hands relaxed and while they applied 80% of their maximum effort for each task. Six degree‐of‐freedom rigid body kinematics of the metacarpal with respect to the trapezium from the unloaded to the loaded task positions were computed in terms of a TMC joint coordinate system. Joint instability was expressed as a function of the metacarpal translation and the applied force. We found that the TMC joint was more unstable during a key pinch task than during a jar grasp or a jar twist task. Sex, age, and early OA did not have an effect on TMC joint instability, suggesting that instability during these three tasks is not a predisposing factor in TMC OA. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1639–1645, 2015.